Pengaruh Promosi, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Transportasi Kereta Api - Tyas Retno Yuniar; Ahadiati Rohmatiah (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
This study aims to find out (1) Is there an influence between promotion and customer satisfaction of rail transportation services at Madiun Besar Station (2) Is there an effect of price on customer satisfaction of rail transportation services at Madiun Besar Station (3) Is there an influence between service quality and customer satisfaction of rail transportation services at Madiu Besar Station. The sample in this study were customers of rail transportation services at the Madiun station with 100 respondents. The sample method used was purposive sampling of primary data using a questionnaire measured using a Likert scale and distributed to 100 respondents. The data analysis technique used classical assumption test, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing using t test and F test. The results showed that (1) promotion, price, and service quality simultaneously had a significant positive effect on customer satisfaction. on rail transportation services at the Madiun big station (2) promotion, price, and service quality simultaneously have a significant positive effect on customer satisfaction on rail transportation services at the Madiun big station.